Pemerhati Perempuan Surabaya - Nurul Hidayati (MUWAZAH : jurnal kajian gender, 2015)
Women's worked has become at usual things in this modern era. They are very diverse reasons, among others: economic conditions, the demands of time and self existence as human beings who have the same ability as men. However, culture is still not in favor of working women encounter resulted in a double burden, which play a role in public and domestic spaces. This double burden became socio-cultural problem and a form of gender in equity with the victims are women.